2003
DOI: 10.21273/horttech.13.2.0252
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Fruit and Vegetables as Healthful: Vitamins and Phytonutrients

Abstract: Plants are the foundation for a significant part of human medicine and for many of the most widely used drugs designed to prevent, treat, and cure disease. Folkloric information concerning traditional remedies for disease has had inestimable value in establishing familial and cultural linkages. During the 20 th century, modern medical science in the U.S. and other developed countries ushered in a new era focused on synthetic medicines. Even though many of these compounds were based on natural compounds found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Awareness for the important role fruits and vegetables have in a healthy diet is increasing,6, 7 as is interest in organic foods.…”
Section: Introductionmentioning
confidence: 99%
“…Awareness for the important role fruits and vegetables have in a healthy diet is increasing,6, 7 as is interest in organic foods.…”
Section: Introductionmentioning
confidence: 99%
“…Onion possesses phytochemicals with health benefi ts beyond nutrition, promoting interest in the relationship between food and well-being (Goldman, 2003). In onion, the preponderant fl avonols are glucose derivates of quercetin: quercetin-3,4´-O-diglucoside and quercetin 4´-O-glucoside (Leighton et al, 1992;Lombard et al, 2002;Price and Rhodes, 1997).…”
mentioning
confidence: 99%
“…As early as 1617, citrus was recommended for the British navy and by the end of the 18th century, limes and sauerkraut were shown to be antiscorbutic. In the 20th century, scientific research demonstrated the occurrence of various vitamins (a word derived from vital amines) or substances required in tiny amounts by various organisms, including humans (Desjardins, 2008;Finley, 2005;Goldman, 2003). Subsequently, fruits and vegetables were shown to be good sources of various vitamins.…”
Section: Health and Horticulturementioning
confidence: 99%